THE EFFECT OF STRANDED ASSETS IMPAIRMENT ON FIRM VALUE: THE MODERATING ROLE OF CLIMATE CHANGE RISK DISCLOSURE TRANSPARENCY WITH APPLIED EVIDENCE FROM EGYPTIAN CEMENT INDUSTRY - Huda M. Abdallah; Samhi Abdelaty Difalla; Mukhtar Suleiman; Abdalaziz M. Alhaggan (International Journal for Quality Research)
The purpose of this study is to analyze the moderating effect of climate change risk disclosure as well as the effect of stranded assets impairment on business value in cement listed firms in the Egyptian environment which consist of 16 firms, the final sample for the study becomes 81 observations for the period between 2017 and 2023. Firm value measured by the Tobin's Q and economic value added. The climate disclosure index was used to determine the disclosure level of climate change risk according to the Egyptian Financial Supervision Authority's decisions. The results of this study indicate that Stranded assets impairments negatively affect the firm value, while, climate change risk disclosure positively affects the firm Value, and moderated relationship for the interaction between the stranded assets impairments and total climate change risk disclosure positively affects the firm value measured by the Tobin's Q and economic value added (EVA).